Chest pain and recurrent chylothorax: an unusual presentation of malignant pleural mesothelioma. Issue 5 (15th June 2017) - Darley, David R.; Granger, Emily; Glanville, Allan R.
Abstract : Malignant mesothelioma presenting with recurrent chylous effusion is rare. We describe the case of a 34‐year‐old female Macedonian immigrant who presented with central chest pain and subsequently a left‐sided chylous pleural effusion. The diagnosis was made on pleural biopsy via video‐assisted thoracoscopic surgery (VATS). Our case demonstrates the utility of thoracic magnetic resonance imaging (MRI) and the difficulties associated with pleural cytology and cervical lymph node biopsy in the establishment of a diagnosis of mesothelioma. It is a reminder that mesothelioma can metastasize to mediastinal and cervical lymph nodes, can occur in young people, and may present as a chylothorax. Abstract : Malignant mesothelioma presenting with recurrent chylous effusion is rare. We describe a young patient who presented with central chest pain and subsequently a left‐sided chylous pleural effusion. The diagnosis was made on pleural biopsy via video‐assisted thoracoscopic surgery (VATS). Our case demonstrates the utility of thoracic magnetic resonance imaging (MRI) and the difficulties associated with pleural cytology and cervical lymph node biopsy in the establishment of a diagnosis of mesothelioma.